Ética e religião em Gilles Lipovetsky: uma análise da obra A sociedade pós-moralista - Costa, Renato de Lima da (2012)
The present dissertation exposes the thought of Gilles Lipovetsky by examining specifically his book The post-moralistic society, in which the author treats in detail the ethical issue in contemporaneity. Under the French philosophical tradition scope, Lipovetsky proposes a study of more specific social phenomenons, by having as central object the hypermodern society. In this society determined by consumption, the ethics puts itself under new parameters. In the book mentioned above, the author is dedicated to understanding the paradoxes that circulate the discussions around the ethical issue, he notes that an ethics of post-obligation, whose purposes is the full satisfaction of the subjective desires of individuals in the most variety of actions, today determines the social relations of individuals in the social spheres. The author's theory concerning to the ethics of post-obligation brings significant elements for a better understanding of the religious issue, especially in its ethical dimension. The contributions of the author pointed to the emergence of a secularized religion to gravitate in the given social setting, whose characteristics are exposed in this dissertation. By opposing the considerations of Lipovetsky with the theories of other authors, it is possible to realize the existence of convergent and divergent points in the ethical proposals that they present. Lipovetsky's analysis shows itself pertinent to the discussion concerning to the possibility of a global ethics, common to all peoples